2020
DOI: 10.1186/s12199-020-00881-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunological status and virological suppression among HIV-infected adults on highly active antiretroviral therapy

Abstract: Background: World Health Organization (WHO) recommends that viral load ([VL) is a primary tool that clinicians and researchers have used to monitor patients on antiretroviral therapy (ART), an antiviral drug against retroviruses. Whereas, CD4 cell counts can only be used to monitor clinical response to ART in the absence of VL testing service. Therefore, this study is aimed to assess the level of immunological status and virological suppression, and identify associated factors among human immunodeficiency viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
1
16
2
2
Order By: Relevance
“…Based on individual and public health benefits consequent to early initiation of ART, together with increased safety and tolerability of antiretroviral strategies, ART is now recommended for all PLWH [4][5][6]. Indeed, although eradication of HIV infection cannot be achieved with current ART, durable plasma HIV RNA suppression minimizes the risk of emergent drug resistance and contributes to restoring immunological function [7][8][9][10]. Due to proven efficacy, safety and ease of administration, integrase strand transfer inhibitors (INSTIs) are recommended for the treatment of HIV infection in many settings [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Based on individual and public health benefits consequent to early initiation of ART, together with increased safety and tolerability of antiretroviral strategies, ART is now recommended for all PLWH [4][5][6]. Indeed, although eradication of HIV infection cannot be achieved with current ART, durable plasma HIV RNA suppression minimizes the risk of emergent drug resistance and contributes to restoring immunological function [7][8][9][10]. Due to proven efficacy, safety and ease of administration, integrase strand transfer inhibitors (INSTIs) are recommended for the treatment of HIV infection in many settings [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral therapy made it possible to decrease the viral load below the sensitivity limit of diagnostic tests, caused an increase in the level of CD4 lymphocytes, and reduced the incidence of opportunistic infections and the development of full-blown acquired immunodeficiency syndrome (AIDS). As a consequence, mortality in HIV patients has decreased significantly [2][3][4]. However, drug-induced side effects associated with longterm antiretroviral therapy are becoming a growing concern [2,3,5].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, mortality in HIV patients has decreased significantly [2][3][4]. However, drug-induced side effects associated with longterm antiretroviral therapy are becoming a growing concern [2,3,5]. HIV therapy involves highly active antiretroviral therapy (HAART), meaning that patients are treated with drug combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the majority of our study participants had good adherence, and they were from urban residences, which might have access to health care facilities that might not require walking long distances to get HIV care services; this could make them to take their medication on time, which would have an impact on the control of viral replication and the improvement of immunological status [38,39].Previous studies have demonstrated that those clients who live far from healthcare facilities where services are offered had delayed healthcare-seeking behavior; this in turn leads to virologic-non suppression [40,41]. The other possible explanation could be that most of our study participants were disclosed their HIV status and had treatment supporters.…”
Section: Discussionmentioning
confidence: 99%